DETERMINASI KINERJA UMKM: ANALISIS PERAN INKLUSI KEUANGAN, LITERASI KEUANGAN DIGITAL, PENGELOLAAN KEUANGAN, DAN LOCUS OF CONTROL - Purwita, Eka Yuli; Innayah, Maulida Nurul; Purwidianti, Wida; Widyaningtyas, Dian (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to examine the effects of financial inclusion, digital financial literacy, financial management, and locus of control on the performance of micro, small, and medium enterprises (MSMEs) in Banyumas Regency, using a Resource-Based Theory framework.Methods: The quantitative methodology of this study is based on primary data collected from 115 respondents, selected at random from a pool of MSME owners, via an online and offline survey.Results: The findings indicate that financial management and locus of control have a positive, significant effect on MSME performance, underscoring the importance of internal managerial capabilities and psychological resources. Conversely, financial inclusion and digital financial literacy do not show a significant impact on MSME performance, suggesting that access to financial services and digital financial tools has not yet been optimally utilized to enhance business performanceConclusion and suggestion: These results imply that financial access alone is insufficient without adequate managerial skills and strong internal controls. Therefore, MSME development programs are encouraged to focus on strengthening financial management practices and internal locus of control to improve MSME performance and sustainability. Keywords: Digital Financial Literacy, Financial Inclusion, Financial Management, Locus of Control, MSME Performance